IPv6 in wireless sensor networks for IoT: Case study in environmental monitoring applications - Pascoal, R.; Galego, N. (8th World Conference on Smart Trends in Systems Security and Sustainability, WorldS4 2024, 2025)
This study investigates the implementation of IPv6 in Wireless Sensor Networks (WSNs) intend-ed for environmental monitoring applications, presenting a comprehensive case study. The transi-tion to IPv6 emerges as a crucial response to address the challenges of addressing, communica-tion efficiency and security in dynamic Internet of Things (IoT) environments. Using a WSN in an environmental monitoring context, this study highlights the effectiveness of IPv6 in providing efficient communication between sensors, guaranteeing unique and global addressing. The case study was conducted in a forest ecosystem, covering critical variables such as temperature, hu-midity, air quality and luminosity. The results indicate remarkable efficiency in data transmission, highlighting IPv6's ability to optimise the exchange of information in real time. In addition, the successful implementation demonstrates substantial improvements in energy conservation, con-tributing to the operational autonomy of the sensors. When considering the scalability of the implementation, fluid integration with the existing IPv6 infrastructure is observed, allowing for modular expansion of the WSN. The critical analysis of security highlights the importance of robust protocols, guaranteeing data integrity and confidentiality in critical environmental monitor-ing environments. Residual issues in the automatic configuration of IPv6 addresses point to areas for continued refinement, especially in relation to energy efficiency. These results provide valua-ble insights for future research and implementations of IPv6 in WSNs, offering a solid basis for improvements in environmental monitoring environments within the overarching Internet of Things scenario.